The Realities of Human Resource Management - Sisson Keith; Storey John (Open University Press, 2003)
This book is written and structured in such a way as to be equally useful to practicing managers (not necessarily specialist human resource managers) and to students who are studying a course or module in human resource management. Preface, Introduction: The Story so Far, Managing Strategically, Managing for High Performance: Organizational Structures and Processes, Involvement and Participation: The Key to Success?, Reshaping the Wage and Work Bargain: Pay and Working Time, Improving Competences and Capabilities I: Training and Development, Improving Competences and Capabilities II: Recruitment and Selection, Managing with Trade Unions, Managing the HR/ IR Function, The Key Issues, References, Index.